Critical Analysis of Healthcare Policy, Governance, And Public Health Strategies - AL Harbi, Naif Mohammed Nasser; Alabaad, Abdullah Baqer; alazwari, Mohammed abdullah; Alaqidi, Ibrahim Hamad Khalifah; Alasmri, Dlaim Ali; Alturaiki, Ahmed Essa; Boujbarah, Mohammad abdullah Hussain; Almuslim, Fatimah Mohammad; Hajjoul, Hassan Ali; Almuhamidh, Mohammed Fahad Hussain (Journal of Ecohumanism, 2024)
Global health and health services delivery require healthcare policy and governance to achieve meaningful enhancements. Good governance makes it possible to provide healthcare services equally, sustainably, and creatively. This review seeks to examine the progressive development of healthcare policies, the relationship between governance and public health, and their impacts on global health. Departing from more recent patterns, this paper illustrates strengths and shortcomings, as well as how strong frames are important to close disparities and foster sustainability.